Semiotic Advertising by International Firms: A Comparative Study of Premium Smart Phone Brands in China, South Korea and USA - Elizabeth Adaobi Oputa; Fakhrorazi bin Ahmad (AIBPM Publisher, 2019)
This paper presents a theoretical discussion regarding how semiotic advertising is adopted by international firms. The semiotic advertising concept as explained in this study is defined as an advertising approach or method based on the use of signs and symbols for the purpose of communicating with a target audience. The signs and symbols act as indirect communicators of messages that firms try to convey to consumers. Since this method of advertising is focused and based on the use of different symbolic features or signs, it was found to be beneficial for cross-cultural advertising by international firms. Therefore, this study evaluated the use of semiotic advertising by two (2) premium smartphone brands in three countries, i.e. South Korea, USA and China. Analysis of different advertisements adopted by these firms in the three countries revealed that there were two underlying factors regarding the use of semiotic advertising. The first factor was definitely the cultural factor, where it was found that Apple’s hidden messages in the advertisements were highly aligned to each country’s cultural aspects and other factors. The other factor established by Samsung was the use of signs to create a special perception about the brand, thus, leading to the development of better relations between the brand and the customer. The findings showed that the use of semiotic advertising by international premium smartphone brands was definitely different across countries.